Oguy A. D., Ivasiuk O. Ya. West and Eastern European translation in the Middle Ages (476-1492): a new attempt of its presentation in the manual of history of translation - Oguy A. D.; Ivasiuk O. Ya. (Philological Treatises, 2020)
This article focuses on a new manual in history of translatology and on new principles of its organization: the explanation of (WHAT? WHEN? HOW? WHY?); the description (periodization; chronological data; phonological names). As an example the history of translation in West and East European Middle Ages period (476-1492) has been described on the basis of prominent translators of this period.